Sssfh1, a Gene Encoding a Putative Component of the RSC Chromatin Remodeling Complex, Is Involved in Hyphal Growth, Reactive Oxygen Species Accumulation, and Pathogenicity in Sclerotinia sclerotiorum - Liu, Ling; Wang, Qiaochu; Sun, Ying; Zhang, Yanhua; Zhang, Xianghui; Liu, Jinliang; Yu, Gang; Pan, Hongyu (Frontiers in Microbiology, 2018)
SFH1 (for Snf5 homolog) protein, comprised in the RSC (Remodels Structure of Chromatin) chromatin remodeling complex, functions as a transcription factor (TF) to specifically regulate gene transcription and chromatin remodeling. As one of the well-conserved TFs in eukaryotic organisms, little is known about the roles of SFH1 protein in the filamentous fungi. In Sclerotinia sclerotiorum, one of the notorious plant fungal pathogens, there are nine proteins predicted to contain GATA-box domain according to GATA family TF classification, among which Sssfh1 (SS1G_01151) encodes a protein including a GATA-box domain and an SNF5 domain. Here, we characterized the roles of Sssfh1 in the developmental process and fungal pathogenicity by using RNA interference (RNAi)-based gene silencing in S. sclerotiorum. RNA-silenced strains with significantly reduced Sssfh1 RNA levels exhibited slower hyphal growth and decreased reactive oxygen species (ROS) accumulation in hyphae compared to the wild-type (WT) strain. Yeast two-hybrid (Y2H) and bimolecular fluorescence complementation (BiFC) assays demonstrated that SsSFH1 interacts with SsMSG5, a MAPK phosphatase in S. sclerotiorum. Furthermore, Sssfh1-silenced strains exhibited enhanced tolerance to NaCl and H2O2. Results of infection assays on soybean and common bean (Phaseolus vulgaris) leaves indicated that Sssfh1 is required for full virulence of S. sclerotiorum during infection in the susceptible host plants. Collectively, our results suggest that the TF SsSFH1 is involved in growth, ROS accumulation and virulence in S. sclerotiorum.